Search for pair production of massive particles decaying into three quarks with the ATLAS detector in √ s = 7 TeV pp collisions at the LHC - Anduaga, Xabier Sebastián (2012)
A search is conducted for hadronic three-body decays of a new massive coloured particle in √s = 7 TeV pp collisions at the LHC using an integrated luminosity of 4.6 fb-1 collected by the ATLAS detector. Supersymmetric gluino pair production in the context of a model with R-parity violation is used as a benchmark scenario. The analysis is divided into two search channels, each optimised separately for their sensitivity to high-mass and low-mass gluino production. The first search channel uses a stringent selection on the transverse momentum of the six leading jets and is performed as a counting experiment. The second search channel focuses on low-mass gluinos produced with a large boost. Largeradius jets are selected and the invariant mass of each of the two leading jets is used as a discriminant between the signal and the background. The results are found to be consistent with Standard Model expectations and limits are set on the allowed gluino mass.